SEMANTIC FEATURE OF PRONOUNS IN THE ENGLISH LANGUAGE - Haitmurodova Muyassar Alisher qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
There are a variety of distinguishing features of English Pronouns. For easy understanding and comprehension, the elements are classified into four maxims, according to Abia (2013). They include: (a) Person, (b) Number, (c) Gender, (d) Case